Microstructures and electrical properties of BSTM multilayers with different periods. Issue 7 (15th May 2016) - Hong, Xuekun; Shao, Tan; Shao, Xueyi; Zhang, Debao; Liu, Yushen; Feng, Jinfu
Abstract: 5% Mn-doped BST (BSTM) multilayers with different periods have been prepared by a chemical solution deposition method. The X-ray diffraction results showed that all of the multilayers exhibited a single perovskite phase, randomly oriented polycrystalline structure. The crystalline qualities improved as the number of periods was increased. The building block consisting of dense and porous BSTM bilayer was characterized and confirmed by transmission electron microscopy (TEM) and spectrometer analysis. Strong frequency dispersion of the dielectric properties was found for all BSTM multilayers. The behaviors of the dielectric losses at high (>450 kHz) and low (<1 kHz) frequencies are related to the extrinsic resonance and the conduction mechanisms, respectively. The dielectric loss peak in the mid-frequency range monotonically decreased with an increase in the number of periods, which was assumed to be attributed to the interactions between the induced space charge polarization and dipolar complexes.